The Situation of Infrastructure Development in Semi-Urban Areas of Nepal - Dhakal, Aishwarya Prasad; Devkota, Bipana (Prajnik Bimarsha प्राज्ञिक विमर्श, 2025)
The main thrust of this paper is to deliver genuine situation of infrastructure within the specific context of development as it is prevailed in semi-urban area of Nepal. Well-developed infrastructure enhances productivity and efficiency projected towards forecasting the economic growth. Policy makers and development agencies have to concern for improved transportation, communication, and energy system to a competitive social environment. Infrastructure development is pre requisite for attractive investment atmosphere and enhances entrepreneurships. The aim of this paper is to depict the related issues of infrastructure related activities and actions as prevailed in the semi-urban area of Birendranagar, Surkhet, Nepal. This paper is based on the qualitative data and information as available from the field and government publications. The term infrastructure primarily denotes two aspects; physical and social infrastructures. This has been argued that both physical and social infrastructure have been inevitable components for the balance development for a contemporary society.